004. Confirming The Diagnosis of Hirschsprung Associated Enterocolitis Based on The Hirschsprung Associated Enterocolitis Guidelines: A Literature Review - Hadi, Kemal Fadhli; Tamba, Riana Pauline (JBN (Jurnal Bedah Nasional), 2024)
Background : Hirschsprung's disease (HD) is one of the most common causes of intestinal obstruction in neonates. One of the most frequently encountered complications, and the leading cause of morbidity and mortality in HD patients, is Hirschsprung-associated enterocolitis (HAEC). In 2017, Gosain et al. developed a guideline to aid in the diagnosis of HAEC, but there are limited studies discussing this guideline and diagnosing HAEC remains unclear. The aim of this study is to establish the diagnosis of HAEC in patients using the HAEC guideline. Methods : The studies were selected from online databases such as Scopus, EBSCOhost, PubMed, ScienceDirect, and Medline. Searches were conducted using Boolean OR and AND. Literature selection was based on abstracts, titles, and keywords. The literature selected were based on predetermined inclusion and exclusion criteria. Results : A total of 1,610 studies were identified from the literature search conducted on five databases using appropriate keywords. The articles were then screened using the PRISMA flow diagram, resulting in the selection of three articles that met the inclusion and exclusion criteria. These three selected studies included two retrospective cohort studies and one literature review and expert consensus study for the diagnosis of HAEC. Conclusion: The HAEC guideline by Gosain et al. can be used to clinically establish HAEC; however, it has not been tested in the population and remains an expert consensus, so its validity as a diagnostic guideline cannot yet be compared to previous scoring methods that have been analyzed in the HAEC patient population.